Kognitivne in duševne motnje v starosti - ocena potreb - Kogoj, Aleš (Zdravniški vestnik, 2008)
Due to longer life expectancy an increase in mental disorders in old age is expected. However, not all diagnostic groups are expected to share equal increase. Methods An estimation of expected number of hospitalizations in 2020was made on the basis of demographic trends. Results In the period 2002-2020 the number of elderly will increase for 35.4 %, number of patients with dementia will increase for 60.1 %, and number of needed hospitalizations 42.6 %. Hospitalizations due to delirium are expected to increase even more, but smaller increase in hospitalizations is expected due to schizophrenia. Conclusions Results are indicating future structure of inpatients with mental disorders and are therefore providing a basis for planning.
Keywords: Aged; Cognition Disorders; Demenca; Dementia; Duševne motnje; Geriatric Psychiatry; Geriatrična psihiatrija; Hospitalizacija; Hospitalization; Mental Disorders; Spoznavne motnje; Starostniki